Unearthing the Figure of Speeches Used in the -R- Album by Rose to Deliver the Messages - Nur Azyza Malik; Ali Mustofa; Ahmad Munir (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This study discussed the use of figure of speech in the song track list of -R- Album that popularized by Rose. The aimed of the study to describe 4 types of figure of speech in the two track lists of the R album; (1) the comparative of figure of speech, (2) the contradiction figure of speech, (3) the affirmation figure of speech, and (4) the satire figure of speech in the collection of both song lyrics. This research was qualitative method with analytical approach. The source of data in this study is the of song lyrics in the -R- album that has two songs entitled “On the Ground and Gone” which contained figure of speech. Reading the lyric was one of the data gathering procedures used in this study; understand the meaning; find the word that contain figure of speech; and describe them. The result of this research was dominated by the contradiction and comparative of figure of speech that found in the both song lyrics if compare to the other figure of speech affirmation and satire. In this study, the researcher studied a song that was dominated by inter minus contradiction and metaphor. The song's writer employed things or objects to convey his or her feelings, which metaphor was given comparative meaning in the song's lyric. Meanwhile, inter minus contradiction prevails in some lyrics, when one sentence contradicts the meaning of the previous statement.